Implementation of Telehealth Services in Rural Schools: A Qualitative Assessment. (21st November 2021) - Fox, Kimberley; Burgess, Amanda; Williamson, Martha Elbaum; Massey, John; Shaler, George; Pearson, Karen; MacKenzie, Jennifer; Merchant, Kimberly; Zhu, Xi; Ward, Marcia
ABSTRACT: BACKGROUND: In rural areas with health professional workforce shortages, telehealth offers an opportunity to address service gaps and meet the health needs of students. Few studies have examined telehealth implementation in rural schools. This study explores facilitators and barriers to the implementation of telehealth programs in rural schools and identifies strategies for successful implementation to inform future school‐based telehealth initiatives. METHODS: We conducted semi‐structured qualitative interviews with 50 key informants involved in the implementation of telehealth programs funded through the School‐Based Telehealth Network Grant Program. Researchers completed a thematic analysis of interview transcripts. RESULTS: The most commonly cited barriers were technology, reimbursement for services, and facilitating acceptance of the telehealth among school staff, clinicians, parents, and students. Key informants identified strategies for facilitating program implementation, including technology training and support, marketing efforts, and integration into existing school processes. CONCLUSIONS: School‐based telehealth can augment clinical capacity in areas with clinician shortages. Entities interested in such an approach to care must engage with their school community to ensure successful implementation. For rural, school‐based telehealth to gain greater adoption and be sustained, these services must be reimbursable by Medicaid and private insurers.